Quantitative Analysis of Neurotransmitter Pathways Under Steady State Conditions – A Perspective - Cooper, Arthur J. (Frontiers in Endocrinology, 2013)
In a contribution to this Research Topic Erkki Somersalo and Daniela Calvetti carried out a mathematical analysis of neurotransmitter pathways in brain, modeling compartmental nitrogen flux among several major participants – ammonia, glutamine, glutamate, GABA and selected amino acids. This analysis is important because cerebral nitrogen metabolism is perturbed in many diseases, including liver disease and inborn errors of the urea cycle. These diseases result in an elevation of blood ammonia, which is neurotoxic. Here, a brief description is provided of the discovery of cerebral metabolic compartmentation of nitrogen metabolism – a key feature of cerebral glutamate-glutamine and GABA-glutamine cycles. The work of Somersalo and Calvetti is discussed as a model for future studies of normal and pathological cerebral ammonia metabolism.